ISTIHDAAMU MUSYAGHILAAT AL WASAITH 3 (MP3) LITANMIYATI MAHAARAH AL ISTIMA’ - Rifqi, Abqoriya (Ijaz Arabi Journal of Arabic Learning, 2018)
We desperately need a good hearing in this life, because if we have a hearing disorder or just a little hearing loss then we will have difficulty in communicating with others. Many language teachers, especially Arabic, ignore the skill of listening lesson.With this research, can be known how far the effectiveness of MP3 usage in learning listening skills of Arabic language, to distinguish the sound of that language. By using the media players 3 (MP3), the researcher can carry out learning listening skill with a nice and fun with the evidence of the students who are more enthusiastic when following the lesson. This medium can only be effective for advanced students with 6% increase in outcomes, but for notice students who have the ability to think slowly it will be ineffective, as evidenced by a decline in value of -6,5%. It is due to the lack of students ability to listen to the voice of native speakers who tend to be fast, and also the dialect used by native speakers is different from the dialect they use every day.